Matrix pixel and Kernel density analysis from the topographic maps - Živković Dragica (The University Thought: Publication in Natural Sciences, 2016)
Complex networks with building density play a significant role in many fields of science, especially in urban sciences. That includes road networks, hydrological networks, computer networks and building changes into geo-space through some period. Using these networks we can solve the problems like the shortest path, the total capacity of networks, density population or traffic density in an urban or suburban area. In this paper for quantifying the complexity of road networks and a novel method for determining building density by using a matrix pixel analysis and Kernel distribution with a concrete example of the city of Belgrade. Both of them represent geo-spatial data. In this case we have analyzed road networks, building density, with the help of specially created software for analyzing pixels on the maps from 1971, including the properties of geo-spatial data we have analyzed from old topographic maps in ratio 1:25.000.